2012
DOI: 10.1007/s00590-012-0944-9
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib inhibits the heterotopic ossification in the rat model with Achilles tenotomy

Abstract: Celecoxib, a selective cox-2 inhibitor, has been shown to prevent the heterotopic ossification following total hip arthroplasty. However, the effects of celecoxib on heterotopic ossification at other locations remain unclear. This study aimed to investigate the effect of celecoxib on heterotopic ossification in the rat model with Achilles tenotomy. Forty male Sprague-Dawley rats, which were randomly divided into 2 groups (n = 20), underwent midpoint Achilles tenotomy on left legs through a posterior approach u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Ossification occurs as a known process in tendon remodelling [ 3 , 11 ]. Zhang et al [ 21 ] showed in a tenotomy rat achilles tendon model investigating the effect of a selective cox2 inhibitor that heterotopic ossification developed in 100 % of the non treated group after 10 weeks. Similar findings are described by Pietschmann et al [ 22 ] in a tendon defect model with the use of polyglycol acid and collagen-type-I scaffolds, seeded with mesenchymal stem cells or tenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Ossification occurs as a known process in tendon remodelling [ 3 , 11 ]. Zhang et al [ 21 ] showed in a tenotomy rat achilles tendon model investigating the effect of a selective cox2 inhibitor that heterotopic ossification developed in 100 % of the non treated group after 10 weeks. Similar findings are described by Pietschmann et al [ 22 ] in a tendon defect model with the use of polyglycol acid and collagen-type-I scaffolds, seeded with mesenchymal stem cells or tenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The Achilles tenotomy rat model has been used to investigate HO prophylaxis and treatment based on its relative simplicity and predictability ( 23 25 ). In the present study, the Achilles tenotomy rat model was employed to investigate how mechanical loading modulates HO in the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…The cause may be similar to HO forming following blast injuries or burns. Although the molecular mechanisms of HO have not been fully elucidated in experimental models [35], inflammatory signaling pathways are speculated to play critical roles in HO formation. Forsberg et al [36] have found an association between a patient's systemic and local inflammatory responses and HO.…”
Section: Discussionmentioning
confidence: 99%